Gastric emptying of solids in patients with cirrhosis: effects of portal hypertensive gastropathy, ascites and serum gastrin levels on gastric emptying - Zehra YILMAZ; Mustafa YILMAZ; Mücahit ATALAY; Neşe EKİNCİ and Belkıs ÜNSAL and Aycan ÜNAL and Himmet KARACA and Sadun KOŞAY (Turkish Journal of Gastroenterology, 2019)
-